Strategies for the Treatment of Parkinson’s Disease: Beyond Dopamine - Iarkov, Alexandre; Barreto, George E.; Grizzell, J. Alex; Echeverria, Valentina (Frontiers in Aging Neuroscience, 2020)
Parkinson’s disease (PD) is the second-leading cause of dementia and is characterized by a progressive loss of dopaminergic neurons in the substantia nigra alongside the presence of intraneuronal α-synuclein-positive inclusions. Therapies to date have been directed to the restoration of the dopaminergic system, and the prevention of dopaminergic neuronal cell death in the midbrain. This review discusses the physiological mechanisms involved in PD as well as new and prospective therapies for the disease. The current data suggest that prevention or early treatment of PD may be the most effective therapeutic strategy. New advances in the understanding of the underlying mechanisms of PD predict the development of more personalized and integral therapies in the years to come. Thus, the development of more reliable biomarkers at asymptomatic stages of the disease, and the use of genetic profiling of patients will surely permit a more effective treatment of PD.